2009
DOI: 10.1371/journal.ppat.1000302
|View full text |Cite|
|
Sign up to set email alerts
|

The Glutathione Biosynthetic Pathway of Plasmodium Is Essential for Mosquito Transmission

Abstract: Infection of red blood cells (RBC) subjects the malaria parasite to oxidative stress. Therefore, efficient antioxidant and redox systems are required to prevent damage by reactive oxygen species. Plasmodium spp. have thioredoxin and glutathione (GSH) systems that are thought to play a major role as antioxidants during blood stage infection. In this report, we analyzed a critical component of the GSH biosynthesis pathway using reverse genetics. Plasmodium berghei parasites lacking expression of gamma-glutamylcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 57 publications
8
82
1
Order By: Relevance
“…In this study, we confirmed that ␥-gcs can be knocked out in P. berghei, similar to a previous report (29). Interestingly, ␥-gcs cannot be knocked out in P. falciparum (32).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we confirmed that ␥-gcs can be knocked out in P. berghei, similar to a previous report (29). Interestingly, ␥-gcs cannot be knocked out in P. falciparum (32).…”
Section: Discussionsupporting
confidence: 92%
“…3A), indicating that loss of ␥-gcs, and not the integration of the Tgdhfr-ts cassette, was responsible for the growth retardation. These results confirm that GSH biosynthesis was important for optimal growth of P. berghei ANKA in vivo (29).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Notably, gammaglutamylcysteine synthase (␥GCS, PFI0925w), an antigen on our Top 20 list, is the rate-limiting enzyme in the synthesis of GSH. The disruption of this biosynthetic pathway caused a minor decrease in parasite growth at the blood stage (possibly because of availability of host GSH) but had severe effects for the parasite at the mosquito stage with arrested development of oocysts and no sporozoite production (66). Pf ␥GCS is expressed in P. berghei sporozoites (31) and host ␥GCS is highly induced in P. yoelii-infected livers (67).…”
Section: Discussionmentioning
confidence: 99%
“…Pictures of oocysts were processed using Adobe Photoshop CS2. Sporozoite counts were performed by salivary gland dissection at day 17 postfeeding based on the work of Vega-Rodriguez et al (31), with the following modifications. Salivary glands from 5 mosquitoes were pooled into 1.5-ml tubes containing 100 l of PBS.…”
Section: Previously Described Methods Involving Ip-rp-uplc-ms/ms (28) mentioning
confidence: 99%